Prevalence of Malnutrition and Nutritional Characteristics of Patients With Inflammatory Bowel Disease. (24th July 2017) - Casanova, María José; Chaparro, Maria; Molina, Begoña; Merino, Olga; Batanero, Ricardo; Dueñas-Sadornil, Carmen; Robledo, Pilar; Garcia-Albert, Ana María; Gómez-Sánchez, Maria Bienvenida; Calvet, Xavier; Trallero, Maria del Roser; Montoro, Miguel; et al.
Abstract: Background and Aims: This study sought to determine the prevalence of malnutrition in patients with inflammatory bowel disease, to analyse the dietary beliefs and behaviours of these patients, to study their body composition, to evaluate their muscular strength and to identify the factors associated with malnutrition in these patients. Methods: This was a prospective, multicentre study. Crohn's disease and ulcerative colitis patients from 30 Spanish centres, from the outpatient clinics, were included. A questionnaire of 11 items was applied to obtain data from patients' dietary behaviour and beliefs. Patients who accepted were evaluated to assess their nutritional status using Subjective Global Assessment and body mass index. Body composition was evaluated through bioelectrical impedance. Results: A total of 1271 patients were included [51% women, median age 45 years, 60% Crohn's disease]. Of these, 333 patients underwent the nutritional evaluation. A total of 77% of patients declared that they avoided some foods to prevent disease relapse. Eighty-six per cent of patients avoided some foods when they had disease activity because of fear of worsening the flare. Sixty-seven per cent of patients modified their dietary habits after disease diagnosis. The prevalence of malnutrition was 16% [95% confidence interval = 12–20%]. In the multivariate analysis, history of abdominal surgery, active disease and avoidance of some foods during flares were associated with higher risk of malnutrition. Conclusions: The prevalence of malnutrition in inflammatory bowel disease patients was high. We identified some predictive factors of malnutrition. Most of the patients had self-imposed food restrictions, based on their beliefs.